Monoclonal Antibodies as Neurological Therapeutics - Gklinos, Panagiotis (Pharmaceuticals (Basel), 2021)
Over the last 30 years the role of monoclonal antibodies in therapeutics has increased enormously, revolutionizing treatment in most medical specialties, including neurology. Monoclonal antibodies are key therapeutic agents for several neurological conditions with diverse pathophysiological mechanisms, including multiple sclerosis, migraines and neuromuscular disease. In addition, a great number of monoclonal antibodies against several targets are being investigated for many more neurological diseases, which reflects our advances in understanding the pathogenesis of these diseases. Untangling the molecular mechanisms of disease allows monoclonal antibodies to block disease pathways accurately and efficiently with exceptional target specificity, minimizing non-specific effects. On the other hand, accumulating experience shows that monoclonal antibodies may carry class-specific and target-associated risks. This article provides an overview of different types of monoclonal antibodies and their characteristics and reviews monoclonal antibodies currently in use or under development for neurological disease.